DNA repair diseases: What do they tell us about cancer and aging? - Menck, Carlos FM (Sociedade Brasileira de Genética, 2014)
The discovery of DNA repair defects in human syndromes, initially in xeroderma pigmentosum (XP) but later in many others, led to striking observations on the association of molecular defects and patients’ clinical phenotypes. For example, patients with syndromes resulting from defective nucleotide excision repair (NER) or translesion synthesis (TLS) present high levels of skin cancer in areas exposed to sunlight. However, some defects in NER also lead to more severe symptoms, such as developmental and neurological impairment and signs of premature aging. Skin cancer in XP patients is clearly associated with increased mutagenesis and genomic instability, reflecting the defective repair of DNA lesions. By analogy, more severe symptoms observed in NER-defective patients have also been associated with defective repair, likely involving cell death after transcription blockage of damaged templates. Endogenously induced DNA lesions, particularly through oxidative stress, have been identified as responsible for these severe pathologies. However, this association is not that clear and alternative explanations have been proposed. Despite high levels of exposure to intense sunlight, patients from tropical countries receive little attention or care, which likely also reflects the lack of understanding of how DNA damage causes cancer and premature aging.